«Don’t kill; nor with hunger nor bullets». Women of selfmanaged welfare kitchens in El Agustino during the political violence - Minaya Rodríguez, Jacqueline (2015)
The self-managed people’s kitchens (CPA) have more than thirty five years of existence since 1978. They are led by brave women who live in a poor, inmigrant and courageous Lima. They struggled with the state for their rights and demands for basic services and food policies. These women made home topics into declared public policies and were able to bear through the economic crisis of the 80s and part of the 90s, showing a highly effective way of organization in a very difficult period. In that very complex context they were able to get along with members of Sendero Luminoso (SL) who entered the shanty towns to «exacerbate contradictions» and applied their war strategies in the name of «justice».This investigation traces the trajectories of former leaders of the CPAs from the district of El Agustino, and presents their testimonies on the political violence that they lived between 1978 and 1992, and on their difficult relations with the State. This coexistence produced a very complex texture of thin threads, where living in proximitywhile keeping distance from SL were part or a more complex process.